3D visualisation of confocal flourescence microscopy data - O'SULLIVAN, CAROL ANN (My University, 2004)
Confocal microscopes are able to non-invasively capture sub-micron details of fluorescent-labelled specimens at multiple depths, but there is a lack of applications capable of displaying this collected information in a meaningful and useful manner. We present a hardware-accelerated volume visualisation application developed for displaying and exploring confocal fluorescence microscopy data. Programmable graphics hardware is employed to improve visual quality and aid in highlighting significant properties of the volume, and an adapted marching cubes algorithm implemented to generate polygonal isosurfaces.
PUBLISHED
Keywords: confocal fluorescence microscopy; computer graphics